“A gente tem muito pra contar!” O território epistemológico camponês por egressos de casas familiares rurais do Brasil e de Portugal - Zimmermann, Angelita (2019)
The Family Centers of Alternation Formation (CEFFA) have been collectively constituted as a movement of struggle and resistance against the impositions of capital and the agribusiness political-economic model. Together, the Rural Family Houses and their territorial production contribute to the formation of what we call the peasant epistemological territory. Since its origin in France, in 1935, this pedagogy and its formative processes have expanded the possibilities of permanence and action of young people in the countryside, through the political-social relations established in the schools' places of action, which, through the interrelation between education and work integrate a transformative praxis into the concrete life of these social subjects. We understand the experience of peasant life from the concepts of sociology of absence and sociology of emergency as a possibility of recognition of the epistemologies of the peasant way of life, which has been denied as modern science by capital. The purpose of this study was to understand the transformations perceived in the (re) production of the lives of the graduates of the High School Rural Family House Three Sales School (CFRTV) - Catuípe, Brazil, and the Campo Verde Agricultural School House (CEACV), Póvoa do Varzim, Portugal, recognizing and visualizing the ecology of knowledges, which unites scientific knowledge to those artisanal / ancestral knowledge, originated from the daily struggle and resistance of these Southern Epistemologies. This research, in a qualitative approach, besides the theoretical and documentary contribution, was instrumented in interviews, experiences and observations, in the schools and in the homes of respondents from each country. It is expected, from the intercultural translation between the studied fields, in Brazil and Portugal, to broaden the understanding of the contradictions of the agrarian question, the formative process of these CEFFAs and its relationship with the lives of the graduates. Thus, we recognize the knowledge about the complex relationship between formation and territorialization of young people in the countryside, inserted in the class struggle and in the confrontation of working and living conditions in the contemporary field.